Evaluasi Penggunaan Sistem Jembatan Timbang Online (JTO) Terintegrasi dengan Metode PIECES Framework - Novie Hari Purnomo (Institut Teknologi Garut, 2023)
ODOL (Over Dimension Over Loading) violations in freight transportation in Indonesia have become a very serious problem. Over Dimension is a condition where the dimensions of the vehicle carrier are not in accordance with production standards and regulatory provisions, while Over Loading is a condition where the vehicle carries a load that exceeds the specified load limit. One of the government's efforts to reduce the number of ODOL (Over Dimension Over Loading) vehicle violations is to apply information technology that can support performance in the UPPKB (Motorized Vehicle Weighing Unit). The Integrated Online Weighbridge System is a distributed system in each UPPKB whose data is centralized in a monitoring system and integrated with other systems to exchange data with the aim of speeding up the process of data collection and inspection of goods transport vehicles. This study aims to describe the effectiveness of supervising goods transport vehicles using the Integrated Online Weighbridge System at UPPKB and obtain information on constraints on the system and provide input for improvements to the JTO system for the future. Specific research locations will be carried out at UPPKB Losarang, Indramayu Regency and UPPKB Balonggandu, Karawang Regency. This study uses the PIECES Framework analysis method. Based on the results and discussion above, it shows that the evaluation of the use of the integrated JTO system using the PIECES Framework method is very effective with an average percentage value of 90%. The validity test showed that 18 questions were declared valid and the reliability test of 18 questions, namely 0.969 > 0.70, was declared reliable. The PIECES Framework method is able to show that there are still points that need attention for improving the integrated JTO system.